Behavioural effects and market dynamics in field and laboratory experimental asset markets - Sandra Andraszewicz; Ke Wu; Didier Sornette (Kiel Institute for the World Economy (IfW), 2019)
A vast literature investigating behavioural underpinnings of financial bubbles and crashes relies on laboratory experiments. However, it is not yet clear how findings generated in a highly artificial environment relate to the human behaviour in the wild. It is of concern that the laboratory setting may create a confound variable that impacts the experimental results. To explore the similarities and differences between human behaviour in the laboratory environment and in a realistic natural setting, with the same type of participants, the authors translate a field study Sornette et al. (under review) with trading rounds each lasting six full days to a laboratory experiment lasting two hours. The laboratory experiment replicates the key findings from the field study but the authors observe substantial differences in the market dynamics between the two settings. The replication of the results in the two distinct settings indicates that relaxing some of the laboratory control does not corrupt the main findings, while at the same time it offers several advantages such as the possibility to increase the number of participants interacting with each other at the same time and the number of traded securities.
Keywords: C90; D47; D80; 330; laboratoy expriment; field experiment; experimental asset market; replication